Nutritional value and biochemical composition of two new tropical polychaete species: Potential use as feed ingredients - Xi Wang; Zhihui Sui; Xiaojuan Xu; Yanchao Chai; Haiqing Wang (Journal of the World Aquaculture Society)
Abstract Polychaetes are a promising intertidal resources due to their widespread distribution, considerable biomass, and high nutrition value. The nutritional profiles of two novel tropical polychaetes species (Marphysa sp. and Halla sp.) were determined. Additionally, comparing nutritional levels of polychaetes with other species and requirements of main aquatic animals, this study aimed to explore their potential as aquaculture feed ingredients. The results revealed that both polychaetes species are nutrient‐rich with significant interspecific variation. Marphysa sp. showed higher protein, total essential amino acid (EAA) ratio (17.32 ± 0.46 mg/g), lipid, eicosapentaenoic acid (EPA; 10.99%), α‐Linolenic acid (ALA; 1.25%), ash and energy content compared to Halla sp. (p < 0.05). Conversely, Halla sp. had a significantly higher docosahexaenoic acid (DHA; 5.68%) index compared to Marphysa sp. (DHA; 2.57%). Meanwhile, the levels of macroelements (K, Ca, Na) and trace elements (Mg, Mn, Cu) also exhibited differences in the two species. Compared with other polychaetes and aquatic feed, both Marphysa sp. and Halla sp. are promising high‐quality feed ingredients, as they contain high levels of minerals, essential amino acids, and beneficial lipid profiles. This study will support the identification of alternative substitutes to meet the growing demand for aquafeed ingredients.